Evaluation and Economics of Some Insecticides for the Control of Mustard Aphid (Lipaphis Erysimi Kalt.) on Raya - Vir, Satya (Annals of Arid Zone, 2016)
Field trials were conducted during rabi 1980-81 and 1981-82 to evaluate the efficacy and economics of insecticides against mustard aphid Lipapltis erysimi Kalt. on mustard crop. The treatment of methyl-demeton (0.025%), phosphamidon (0.25%) and monocrotophos (0.25%) proved to be the best in reducing the aphid population and increasing the seed yield of the crop. The net return in rupees was also maximum (Rs. 1309.90 to Rs. 1479.95ha) on treatment of methyldemeton, phosphamidon and monocrotophos in both the years and are therefore, recommended for the control of mustard aphid under agro-c1imatic conditions of Rajasthan.